Neuroprotective effects of flavonoids: endoplasmic reticulum as the target - Amiri, Bita; Yazdani Tabrizi, Maryam; Naziri, Mahdyieh; Moradi, Farzaneh; Arzaghi, Mohammadreza; Archin, Iman; Behaein, Fatemeh; Bagheri Pour, Anahid; Ghannadikhosh, Parna; Imanparvar, Saba; Akhtari Kohneshahri, Ata; Sanaye Abbasi, Ali; et al. (Frontiers in Neuroscience, 2024)
The incidence of neurological disorders, particularly age-related neurodegenerative pathologies, exhibits an alarming upward trend, while current pharmacological interventions seldom achieve curative outcomes. Despite their diverse clinical presentations, neurological diseases often share a common pathological thread: the aberrant accumulation of misfolded proteins within the endoplasmic reticulum (ER). This phenomenon, known as ER stress, arises when the cell's intrinsic quality control mechanisms fail to cope with the protein-folding burden. Consequently, misfolded proteins accumulate in the ER lumen, triggering a cascade of cellular stress responses. Recognizing this challenge, researchers have intensified their efforts over the past two decades to explore natural compounds that could potentially slow or even reverse these devastating pathologies. Flavonoids constitute a vast and heterogeneous class of plant polyphenols, with over 10,000 identified from diverse natural sources such as wines, vegetables, medicinal plants, and organic products. Flavonoids are generally divided into six different subclasses: anthocyanidins, flavanones, flavones, flavonols, isoflavones, and flavonols. The diverse family of flavonoids, featuring a common phenolic ring backbone adorned with varying hydroxyl groups and additional modifications, exerts its antioxidant activity by inhibiting the formation of ROS, as evidenced by research. Also, studies suggest that polyphenols such as flavonoids can regulate ER stress through apoptosis and autophagy. By understanding these mechanisms, we can unlock the potential of flavonoids as novel therapeutic agents for neurodegenerative disorders. Therefore, this review critically examines the literature exploring the modulatory effects of flavonoids on various steps of the ER stress in neurological disorders.